1990
DOI: 10.1021/bi00465a033
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the Escherichia coli Gal repressor protein with its DNA operators in vitro

Abstract: The binding of Escherichia coli Gal repressor to linear DNA fragments containing two binding sites (OE and OI) within the gal operon was analyzed in vitro with quantitative footprint and mobility-shift techniques. In vivo analysis of the regulation of the gal operon [Haber, R., & Adhya, S. (1988) Proc. Natl. Acad. Sci. U.S.A. 85, 9683-9687] has suggested the role of a regulatory "looped complex" mediated by the association of Gal repressor dimers bound at OE and OI. The binding of Gal repressor to a single sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
70
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 57 publications
7
70
0
Order By: Relevance
“…In this paper we have shown that IclR protein is susceptible to various kinds of proteolytic degradation during purification and have established a method of preparing useful amounts of the intact, full-length molecule. The full-length preparations bind to operator DNA with only moderate affinity, showing a half-maximal binding at 3.6 x 10"O M protein, in comparison with other well-characterized repressors where the Kd values fall in the range 10"o-10"2 M (e.g., Vershon et al, 1987;Carey, 1988;Brenowitz et al, 1990). IclR binding of operator is 44-fold weaker when the N-terminal eight or nine amino acids are missing, suggesting that this region contributes significantly to DNA binding.…”
Section: Spectroscopic Properties Of Iclr Protein and Native Moleculamentioning
confidence: 76%
“…In this paper we have shown that IclR protein is susceptible to various kinds of proteolytic degradation during purification and have established a method of preparing useful amounts of the intact, full-length molecule. The full-length preparations bind to operator DNA with only moderate affinity, showing a half-maximal binding at 3.6 x 10"O M protein, in comparison with other well-characterized repressors where the Kd values fall in the range 10"o-10"2 M (e.g., Vershon et al, 1987;Carey, 1988;Brenowitz et al, 1990). IclR binding of operator is 44-fold weaker when the N-terminal eight or nine amino acids are missing, suggesting that this region contributes significantly to DNA binding.…”
Section: Spectroscopic Properties Of Iclr Protein and Native Moleculamentioning
confidence: 76%
“…Similar DNA looping by LacI has also been shown with synthetic DNA templates carrying two lac operators (Krämmer et al 1987;Eismann & MĂźller-Hill 1990). The fact that, in a purified system, the dimeric GalR is not as effective as tetrameric LacI in bringing about gal repression warranted the search for a factor that assists GalR in mediating coordinated repression of both P1 and P2, presumably via DNA looping (Brenowitz et al 1990;Choy & Adhya 1992). This paper shows the isolation of such a factor as the histone-like protein HU.…”
Section: Discussionmentioning
confidence: 91%
“…3B), which implies that the repressor inhibits the first phosphodiester bond formation or a step prior to that-i.e., the formation or the activity of the initial transcribing complex (20 (13,16,25). Under the conditions used in our transcription assays, the corresponding operators are fully cpied byl I"I and GaIR+ (16,24).…”
Section: Resultsmentioning
confidence: 99%